Upaya Peningkatan Kemampuan Praktik Sholat Wajib Melalui Metode Demonstrasi Di TPQ Al - Mujahidin Desa Kaleng - Rachmati, Kurnia Yuni; Fitroh, Nur Nihayatul; Fatimah, Siti; Subarkah, Imam (IAINU Kebumen, 2022)
Abstract This study aims to determine the improvement of students' abilities about prayer movements and prayer readings through the demonstration method for class I at TPQ Al-Mujahidin, Kaleng Village. This research is a classroom action research that was carried out for 2 cycles, each cycle consisting of 2 meetings. Each cycle consists of stages of planning, implementation, observation, and reflection. The research subjects were students of class I TPQ Al-Mujahidin Kaleng Village. Data collection techniques using tests, observations, and interviews. The validity of the data using the triangulation technique. The results of the analysis show that in the first cycle of learning as many as 84.61% have been completed. While in the second cycle of learning as many as 84.62% of students have completed in understanding the prayer material. So it can be concluded that there is an increase in students' understanding of the prayer material through the demonstration method. Keywords: prayer, demonstration